Application of The Overall Equipment Effectiveness (OEE) Method in Increasing The Efficiency Of Mangel / Crepper Machine - Fadli Muhammad (Journal of Engineering Science and Technology Management (JES-TM), 2021)
Riau Crumb Rubber Factory (PT. RICRY) is a manufacturing company engaged in processing raw rubber into semi-finished goods. The raw materials used are Ojol and Lump which come from rubber farmers in the Riau area themselves. The products produced consist of two types based on their quality, namely SIR 10 and SIR 20 which will be reprocessed as raw materials for making tires. This product will be exported to various countries such as America, Singapore, South Korea, Australia, Japan, China and so on. This company has a production target of 20,000 tons/year. Based on data in 2014, the company's production only reached 88.33%, which was 17,666.775 tons/year. One of the causes of not achieving the production target was due to problems at the milling station, namely the Mangel/Crepper machine. The large number of raw materials that will go through the milling process causes the Mangel/Crepper machine to operate beyond its capacity. This production process takes place over a long period of time, causing damage to the main engine components such as Bearings, roll grinders, and Dynamo, resulting in Downtime in the production process. Several factors cause problems in the Mangel/Crepper machine, namely human factors, machines, methods, and raw materials. Therefore, the calculation of efficiency on the Mangel/Crepper machine was carried out using the Overall Equipment Effectiveness (OEE) method. It aims to increase production yields. Based on the calculation results, the average Availability Ratio value is 96.512%, the Performance Efficiency Ratio value is 94.835%, the Rate of Quality Product value is 100% and the OEE value of the Mangel/Crepper machine is 91.528%. These values ​​generally meet international standards for each variable. However, the Performance Efficiency Ratio value still does not meet the existing international standards, so it is necessary to make improvements so that the Performance Efficiency Ratio of the Mangel/Crepper machine can reach the international standard values ​​that have been set.